2020
DOI: 10.1016/j.ccell.2020.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Cell Lineage-Based Stratification for Glioblastoma

Abstract: Highlights d Tumor suppressor loss in NSCs and OLCs generate distinct murine GBM subtypes d Human GBM subtypes identified based on speciesconserved transcriptional profiles d Mouse and human cell lineage subtypes exhibit distinct tumor properties d OLC-associated GBMs show ERBB3 dependence and unique therapeutic sensitivity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 71 publications
4
81
0
Order By: Relevance
“…We performed an in silico analysis in order to find TFs overexpressed in EGFRmut gliomas but with a similar expression in wild-type or amplified EGFR gliomas. The best hit was the Sex-determining region Y (SRY)-box 9 (SOX9) gene ( Figure S6A), which have been previously linked to EGFR (22,23). We found a strong upregulation of the SOX9 protein ( Figure 6A) and mRNA ( Figure 6B) in those PDXs harboring EGFR mutations.…”
Section: Egfr Mutations Modulate the Vascular Properties Of Glioma Cementioning
confidence: 80%
“…We performed an in silico analysis in order to find TFs overexpressed in EGFRmut gliomas but with a similar expression in wild-type or amplified EGFR gliomas. The best hit was the Sex-determining region Y (SRY)-box 9 (SOX9) gene ( Figure S6A), which have been previously linked to EGFR (22,23). We found a strong upregulation of the SOX9 protein ( Figure 6A) and mRNA ( Figure 6B) in those PDXs harboring EGFR mutations.…”
Section: Egfr Mutations Modulate the Vascular Properties Of Glioma Cementioning
confidence: 80%
“…Through a cross-species GSC-based stratification approach applying the mouse cell of origin (MCO) gene signature of differentially expressed genes on a large collection of human GSC cultures, we found that developmental origin could be used to stratify functionally distinct groups of patient-derived GSC cultures 22 . A recent similar cross-species approach has further corroborated the importance of cell lineage origin in GBM 23 . In all this has demonstrated that inter-tumor heterogeneity to a large extent is shaped by the intrinsic properties of the GBM cell of origin which result in highly dynamic GSCs that basically evade all current therapies.…”
Section: Introductionmentioning
confidence: 80%
“…Collectively, the cell-of-origin and subsequent mutant cell behavior appear to underlie different biological and genomic phenotypes in GBM. A recent study demonstrated that distinct characteristics in transcriptome profiles, obtained from GBM animal models targeting either NSCs or oligodendrocyte lineage cells, can be used to classify IDH-wildtype GBMs into two subtypes based on the cellular origin ( 58 ). However, individual cells from the same tumor harbor different mutations and exhibit diverse transcriptional patterns and phenotypes ( 59 ), making it difficult to completely unravel cellular origins and tumor evolution processes.…”
Section: Cell-of-origin In Glioblastomamentioning
confidence: 99%